The call to endless adventure: The dynamic unending ascent into God and virtual worlds. Issue 4 (13th October 2019) - Wise, Joshua
Abstract: This article brings together the ideas of Epektasis, dynamic heavenly hierarchy, and adventure to discuss the nature of the expected heavenly new creation. Considering the idea of Epektasis as a never‐ending upward striving into God understood through the work of Joseph Campbell, adventure is used as a descriptive analogy for this process of delving more deeply into God as a community. Virtual worlds, especially video games, are presented as a contemporary metaphor for the invitation to adventure offered by a community's vision of joy and engagement with creation.